Does the use of outsiders' fund enhance shareholders' wealth? Evidence from Nigeria - J. U. J. Onwumere; Imo G. Ibe; Frank O. Ozoh (Journal of Finance and Investment Analysis, 2012)
This paper is an attempt to extend the analysis of the links between the firm's financial structure and the objectives of the firm in maximizing shareholders' wealth. In theory, the financial goal of the firm should be shareholders' wealth maximization as reflected in the book value and the market value of the firm's share. However it is a challenge to management in our world of complex economic environments to achieve this objective. It is against this background that this paper empirically examined the impact of outsiders fund on the firms' shareholders wealth maximization objective using three value maximization indicators; net profit margin viz dividends per share and current ratio from 2004 to 2008 in the Nigerian economy. The study reveals that outsider fund has a positive though not significant impact on dividend per share and current ratio though it was negative and significant impact on net profit margin. Therefore, the study recommends the use of outsiders fund in the financial mix of firms as to magnify shareholders' wealth but an optimal level of outsiders' contribution should be sought for by management. This will reduce the possibility of trading on the equity of shareholders which may lead to bankruptcy of the firm.
Keywords: G32; 330; debt financing; shareholders' wealth maximization; firms' value